2020
DOI: 10.3389/fendo.2020.00226
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Peptides and Their GPCRs in the Peppermint Shrimp Lysmata vittata, a Protandric Simultaneous Hermaphrodite Species

Abstract: Peptide hormones commonly binding with G-protein coupled receptors (GPCRs) achieve their function in reproduction. The peppermint shrimp Lysmata vittata popular in marine ornamental trade and is known to display protandric simultaneous hermaphrodite (PSH). Knowledge on reproductive biology of this commercial species is critical for resources management and aquaculture. This study employed Illumina sequencing and bioinformatics analysis to identify peptides and their candidate GPCRs from male phase (MP) and euh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 77 publications
(146 reference statements)
1
19
1
Order By: Relevance
“…Importantly, our study was the first to indicate that certain neuropeptides in prawns play an important role in response to salinity acclimation. Interestingly, some neuropeptide transcripts that were detected previously in other decapod crustacean species were not identified in this M. nipponense transcriptome, such as crustacean female sex hormone (CFSH) (27,28). Notably, our previous M. nipponense de novo transcriptome assembly did include these neuropeptides, which partially disagrees with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, our study was the first to indicate that certain neuropeptides in prawns play an important role in response to salinity acclimation. Interestingly, some neuropeptide transcripts that were detected previously in other decapod crustacean species were not identified in this M. nipponense transcriptome, such as crustacean female sex hormone (CFSH) (27,28). Notably, our previous M. nipponense de novo transcriptome assembly did include these neuropeptides, which partially disagrees with the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Following a previous transcriptome study, two ILP transcripts, Lvit-IAG1 and Lvit-IAG2, exist in the PSH shrimp, L. vittata ( Bao et al, 2020). Lvit-IAG1 has also been identified as an IAG via functional study (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…The very low but detectable expression of Lw-IAG during the euhermaphrodite phases suggested that Lw-IAG was possibly responsible for the maintenance of the male reproductive activity in euhermaphrodite phase. Recently, a transcriptomic study identified two insulin-like peptide (ILP) transcripts (Lvit-IAG1 and Lvit-IAG2) in the peppermint shrimp Lysmata vittata (Bao et al, 2020), and biological functions of Lvit-IAG1 have been explored in detail (Liu et al, 2020). In L.vittata, silencing Lvit-IAG1 impeded development of male-related phenotypes (appendices masculinae (AM) and male gonopores) while suppressing the germ cells at the primary spermatocyte stage, demonstrating that Lvit-IAG1 was indeed a functional IAG.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of recent transcriptomes has added another level of complexity by identifying a new form of peptide belonging to the superfamily ( 45 , 109 , 110 ). These new sequences possess the six conserved cysteine residues, but do not have a PRP sequence, nor a dibasic cleavage site or the glycine residue, a signature of MIH ( 45 ).…”
Section: Evolution and Structural Diversification Of The Superfamilymentioning
confidence: 99%